“Nano-Biomaterials” – A New Approach Concerning Multi-Drug Resistant Tuberculosis (MDR-TB) - Saravanan, Muthupandian; Duche, Kebret; Asmelash, Tsehaye; Gebreyesus, Araya; Negash, Letemichael; Tesfay, Amanuel; Hailekiros, Haftamu; Niguse, Selam; Gopinath, Venkatraman; K. Barik, Sisir (Pharmaceutical Nanotechnology, 2015)
Nanotechnology has proved to be a promising tool for the whole scientific community by creating new and superior therapeutic ways for advanced treatment of various diseases. In this sprouting world, the potential application of nanoparticle-based aerosol vaccines for tuberculosis (TB) has been a remarkable and striking breakthrough. The existing administration for at least six months of TB treatment is complicated and needs an extreme transformation. Use of potential Nanomedicine confirmed itself as an effective tool in curing most of the deadly diseases and this has moreover, elevated a hope to encounter TB effectively. Nanomedicines can be used at a larger scale with comparatively low cost and this review has focused on the impact of the nanoparticles against Multi-Drug Resistant tuberculosis (MDR-TB). It also observes the existing TB diagnostic attempts and healing procedures by nanotechnological applications and highlighted the recent advancement in anti-TB drug (ATD) delivery, encapsulation and its systems. As limited therapeutic options are available for TB healing, the appearance of MDR-TB is very much attached to human deaths all over the world and this in turn, is creating a high alarm about the prospect of a future TB epidemic along with the spread of drug-resistant TB.
Keywords: drug delivery